Individual minority shareholder activism approaches and the exit-voice-loyalty neglect model - Othman, Sarina; Ho, Jo Ann; Abdul Latiff, Ahmed Razman (Universiti Malaysia Sarawak, 2019)
This study seeks to better understand engagement of individual minority shareholder activism in developing countries; in the context of this study, Malaysia. Our findings, from 15 interviews with the individual minority shareholders, suggested that the activism approaches adopted by these shareholders are carefully made based on the significant impacts they carry. Utilising the Exit-Voice-Loyalty-Neglect Model, it was discovered that both “Exit” and “Voice” were considered as the two activism approaches mainly adopted by individual minority shareholders in this study. This study provides empirical support that future studies should recognise the individual minority shareholder activism and they may adopt different approaches for such efforts as compared to other groups of shareholders. Further, this study had utilised Exit-Voice-Loyalty-Neglect Model to categorise the identified approaches and extended our understanding of how this model could be used to explain shareholder activism. The various activism approaches identified and categorised accordingly can offer insight to the corporate boards and managers on the future activism behaviour of individual shareholder and be able to offer proper response strategies to such activism approaches.